(untitled) (Asian Journal of Ethnobiology, 2025)
Abstract. Taqwim MHA, Fitriawan MN, Ibriza NM, Fil’ardiani NU, Arifiani KN, Sutomo, Setyawan AD. 2025. Ethnoecological perspectives on biodiversity conservation in volcanic landscapes of Mount Merapi National Park, Central Java, Indonesia. Asian J Ethnobiol 8: 104-115. Volcanic protected areas such as Mount Merapi National Park (TNGM) in Indonesia hold exceptional ecological and cultural significance yet face complex conservation challenges due to ecological volatility and socio-economic vulnerability. This study explores ethnoecological perspectives on biodiversity conservation among residents of Tegalmulyo and Sidorejo, two villages located in the national park’s buffer zone. Using a qualitative descriptive approach, data were collected through structured interviews with 87 respondents, supported by culturally adapted questionnaires and field observations. Results reveal high levels of community awareness regarding biodiversity regulations and intergenerational heritage values. Conservation is widely perceived as a moral and cultural obligation, expressed through non-extractive practices, taboos, and collective activities such as tree planting and forest monitoring. Local belief systems, including spiritual reverence for forested landscapes and communal ethics such as gotong royong, emerge as key drivers of conservation behavior. The study underscores the crucial role of community engagement in biodiversity conservation, as demonstrated by the sustained initiatives of these communities through social cohesion and informal institutions such as the Fire Care Community (Masyarakat Peduli Api/MPA) and Forest Police Partner Community (Marakat Mitra Polhut/MMP). Unlike previous studies, this research provides in-depth ethnoecological insights from disaster-prone volcanic regions, emphasizing culturally embedded conservation practices that remain underexplored in formal policy discourses. The findings highlight the need to incorporate local ecological knowledge and community values into co-management strategies for more inclusive and adaptive biodiversity governance.